A 13.96‐kb chromosomal deletion of two genes is responsible for the tomato seed size in watermelon (Citrullus lanatus). (9th August 2021) - Li, Na; Kong, Shengnan; Zhou, Dan; Shang, Jianli; Wang, Jiming; Li, Nannan; Liu, Lifeng; Ma, Shuangwu
Abstract: Seed size is an important agronomic trait in watermelon, but the candidate genes and underlying molecular mechanism are not fully known. In the present study, genetic analysis of the BC1 population derived from two parental lines revealed that watermelon seed size is controlled by a single locus and medium seeds are dominant to tomato seeds. In addition, we constructed a genetic linkage map. The total length of the linkage map was 1629.92 cM, with an average distance of .16 cM. QTL mapping and resequencing analysis identified a 13.96‐kb chromosomal deletion on chromosome 2. There were only two genes (Cla97C02G045390 and Cla97C02G045400) present in the corresponding region. Transcriptome data of tomato seed and medium seed watermelons showed that the two genes were always highly expressed in medium seed plants but expressed at low or no levels in tomato seed plants. Moreover, two markers indicated that the genes were related to watermelon seed size. Our present study provides key genetic variation and potential candidate gene of watermelon seed size and lays the foundation for the molecular mechanism of seed size.